2021
DOI: 10.1007/s10029-021-02393-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of incisional hernia at the site of stoma closure with different reinforcing mesh types: a systematic review and meta-analysis

Abstract: Purpose To evaluate safety and efficacy of a mesh reinforcement following stoma reversal to prevent stoma site incisional hernia (SSIH) and differences across the prostheses used. Methods A systematic search of PubMed/MEDLINE, EMBASE, SCOPUS and Cochrane databases was conducted to identify comparative studies until September 2020. A meta-analysis of postoperative outcomes and a network meta-analysis for a multiple comparison of the prostheses with each oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…No surgical site occurrence was reported within the mean follow up time of 20 months [ 12 ]. In a recent systematic review, the use of prophylactic mesh was considered safe in terms of SSI, seroma and anastomotic leakage [ 13 ]. Additionally, mesh decreased the hernia rate compared to non-mesh closure.…”
Section: Introductionmentioning
confidence: 99%
“…No surgical site occurrence was reported within the mean follow up time of 20 months [ 12 ]. In a recent systematic review, the use of prophylactic mesh was considered safe in terms of SSI, seroma and anastomotic leakage [ 13 ]. Additionally, mesh decreased the hernia rate compared to non-mesh closure.…”
Section: Introductionmentioning
confidence: 99%
“…Severe SSIH even requires multiple surgeries, which greatly increases the patient’s economic burden and mental suffering. Currently, the incidence of SSIH varies among different studies, which may be closely related to follow-up time and disease type [ 11 , 12 ]. Tilney et al [ 13 ] reported that the probability of recurrent incisional hernia after ileostomy was 3.7%, and the probability of recurrent incisional hernia after colostomy was 14.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Biological meshes, typically made of porcine collagen which degrades over time, are available and have been examined in the context of this operation [8][9][10]. However, these are expensive and take-up of these products for this operation has been slow within colorectal practice.…”
Section: Introductionmentioning
confidence: 99%